2007
DOI: 10.1074/jbc.m610357200
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Cellular NAD Levels by Nicotinic Acid and Involvement of Nicotinic Acid Phosphoribosyltransferase in Human Cells

Abstract: NAD plays critical roles in various biological processes through the function of SIRT1. Although classical studies in mammals showed that nicotinic acid (NA) is a better precursor than nicotinamide (Nam) in elevating tissue NAD levels, molecular details of NAD synthesis from NA remain largely unknown. We here identified NA phosphoribosyltransferase (NAPRT) in humans and provided direct evidence of tight link between NAPRT and the increase in cellular NAD levels. The enzyme was abundantly expressed in the small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
180
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(190 citation statements)
references
References 48 publications
8
180
1
1
Order By: Relevance
“…Moreover, in additional experiments on brush border membrane vesicles of human jejunum, they confirmed a strict pH dependence of nicotinate reabsorption, being higher at low pH. This is consistent with our observation of a pH dependence of hOAT10, Nicotinate may serve not only for NAD Ï© synthesis, which is important for energetic processes, signal transduction pathways, or even the activation of the NAD Ï© -dependent histone deacetylase SIRT1 and therefore life extension (42), but also for reabsorption of the purine metabolite urate.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, in additional experiments on brush border membrane vesicles of human jejunum, they confirmed a strict pH dependence of nicotinate reabsorption, being higher at low pH. This is consistent with our observation of a pH dependence of hOAT10, Nicotinate may serve not only for NAD Ï© synthesis, which is important for energetic processes, signal transduction pathways, or even the activation of the NAD Ï© -dependent histone deacetylase SIRT1 and therefore life extension (42), but also for reabsorption of the purine metabolite urate.…”
Section: Discussionsupporting
confidence: 90%
“…In higher eukaryotes, two major biochemical pathways, the salvage and the de novo pathway, are involved in the biosynthesis of NAD Ï© . The salvage pathway operates via the two major pathways using nicotinamide phosphoryltransferase (NAMPT) and nicotinamide phosphoribosyltransferase 1 (NAPRT1), which use nicotinamide and nicotinic acid (NA), respectively, as the substrate for NAD Ï© recycling (18). Although both pathways are employed to generate NAD Ï© , in cells expressing endogenous NAPRT1, only the NA added in the salvage pathway can increase cellular levels of NAD Ï© and reduce cytotoxicity by an oxidizing agent (18,19).…”
mentioning
confidence: 99%
“…The salvage pathway operates via the two major pathways using nicotinamide phosphoryltransferase (NAMPT) and nicotinamide phosphoribosyltransferase 1 (NAPRT1), which use nicotinamide and nicotinic acid (NA), respectively, as the substrate for NAD Ï© recycling (18). Although both pathways are employed to generate NAD Ï© , in cells expressing endogenous NAPRT1, only the NA added in the salvage pathway can increase cellular levels of NAD Ï© and reduce cytotoxicity by an oxidizing agent (18,19). GMX1778 (CHS 828; teglarinad) is a potent inhibitor of NAMPT that exerts a cytotoxic effect by decreasing the cellular level of NAD Ï© (20,21).…”
mentioning
confidence: 99%
“…These agents can involve superoxide free radicals, hydrogen peroxide, singlet oxygen, nitric oxide (NO), and peroxynitrite (Chong, et al, 2005e). Most species are produced at low levels during normal physiological conditions and are scavenged by endogenous antioxidant systems that include superoxide dismutase, glutathione peroxidase, catalase, and small molecule substances such as vitamins C and E. Other closely linked pathways to oxidative stress may be tempered by different vitamins, such as vitamin D 3 (Regulska, et al, 2007) and the amide form of niacin or vitamin B 3 , nicotinamide (Chlopicki, et al, 2007, Chong, et al, 2002d, Hara, et al, 2007, Ieraci and Herrera, 2006.Throughout the body, cell survival and lifespan is tied to the presence of oxidative stress and the subsequent induction of apoptotic cell injury , De Felice, et al, 2007, Lin and Maiese, 2001). It has recently been shown that genes involved in the apoptotic process are replicated early during processes that involve cell replication and transcription, suggesting a much broader role for these genes than originally anticipated (Cohen, et al, 2007).…”
mentioning
confidence: 99%